2000
DOI: 10.1161/01.cir.101.8.899
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Left Ventricular Diastolic Filling and Accumulation of Myocardial Collagen at Insulin-Resistant Prediabetic Stage of a Type II Diabetic Rat Model

Abstract: Background-Considerable controversy exists regarding impairment of cardiac function in diabetes mellitus (DM). We investigated the serial changes in left ventricular (LV) histopathology and LV filling dynamics in Otsuka Long-Evans Tokushima Fatty (OLETF) rats, which have been established as an animal model of type II DM. Methods and Results-In 54 OLETF and 54 non-DM rats, body weight, blood pressure, heart rate, and transmitral pulsed Doppler examinations were performed from 5 to 47 weeks of age. An oral gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
202
4
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(235 citation statements)
references
References 26 publications
17
202
4
11
Order By: Relevance
“…Relaxation abnormality in the diabetic heart has been found in clinical studies as well as experimental investigations [28,29]. Another study [30] recently reported that an increase of interstitial collagen and diastolic filling abnormalities appeared in the pre-diabetic stage in OLETF rats. However, in the diabetic stage at 47 weeks of age, the amount of interstitial collagen and LV diastolic function in OLETF rats was not different from LETO rats.In contrast, no collagen accumulation in the extracellular matrix of the heart or LVEDP and LVDd abnormalities were found in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Relaxation abnormality in the diabetic heart has been found in clinical studies as well as experimental investigations [28,29]. Another study [30] recently reported that an increase of interstitial collagen and diastolic filling abnormalities appeared in the pre-diabetic stage in OLETF rats. However, in the diabetic stage at 47 weeks of age, the amount of interstitial collagen and LV diastolic function in OLETF rats was not different from LETO rats.In contrast, no collagen accumulation in the extracellular matrix of the heart or LVEDP and LVDd abnormalities were found in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Another explanation is that histological changes in the left ventricular and aortic wall in diabetic patients may contribute to the correlation between left ventricular diastolic function and aortic stiffness. Several studies of diabetic cardiomyopathy have demonstrated an accumulation of myocardial collagen leading to interstitial and perivascular fibrosis, which correlate with left ventricular early diastolic and systolic dysfunction (3,30). In addition, there have been some reports that collagen accumulation may contribute to aortic wall stiffness in the type 2 diabetic rat model, which would accelerate the aging process in the aortic wall (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…At 30 weeks of age, blood was sampled from the right jugular vein after an overnight fast and the oral glucose (2 g kg À1 body weight) tolerance test (OGTT) was applied as described elsewhere. 10,11,17 Then, all the rats were killed after administering deep anesthesia with i.p. sodium pentobarbital (50 mg kg À1 ), and the heart, aorta and epididymal WAT were excised.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…24 This strain manifests obesity, elevated BP, insulin resistance and dyslipidemia, and thus well serves as a model of metabolic syndrome. 10,11 We and others showed the consequences of such metabolic abnormalities, including impaired coronary-vasodilatory function 19 and left ventricular-diastolic dysfunction, 17 which were attributable to impaired nitric oxide/superoxide balance and enhanced expression of redox-sensitive prolifero-inflammatory cytokines. 10,11,17 The decreased cardiac content of DHFR and increased superoxide production in the aortic wall shown in this study adds new evidence for the accentuated oxidative stress in this model.…”
Section: Oletf Rats As a Model Of Metabolic Syndromementioning
confidence: 99%